Axial loading capacity of concrete‐jacketed RC columns with pre‐ and post‐corrosion damage. (23rd August 2016) - Zhao, Yuxi; Zhang, Dawei; Shen, Shijun; Ueda, Tamon
Abstract: The main objective of this study is to investigate the effect of pre‐ and post‐jacketing corrosion and loading damage on concrete‐jacketed reinforced concrete (RC) columns under uniaxial loading and to develop a methodology for predicting the corresponding compressive strength. The pre‐ and post‐damage involved preloading up to 50 % of the peak load of the core column, an electrochemical process to accelerate the migration of chlorides from an external electrolyte into the test columns and a wetting–drying cycle process with a controlled current to speed up the corrosion of the steel reinforcing bars in the test columns. Uniaxial loading tests were performed to determine the structural performance of the concrete‐jacketed columns with and without corrosion damage. The failure mode and load–displacement and load–strain responses of the test columns were recorded, and the related mechanisms are discussed. A model capable of evaluating the compressive strength of unjacketed or jacketed RC columns with and without corrosion damage was then developed. The analytical approach considered the effect of reinforcement corrosion on the effective loadbearing area of the concrete and the confinement effect of the stirrups. The analytical results agree well with the experimental results, indicating the reliability and effectiveness of the models developed.